Current Tendencies in English and American Studies in Central Europe. Review of Hungarian Journal of English and American Studies Spring, 2020. Vol 26, No 1. and Ad Americam. Journal of American Studies, 2020. Vol. 21. - Szélpál , Lívia (AMERICANA E-journal of American Studies in Hungary, 2020)
Hungarian Journal of English and American Studies, Spring, 2020, Vol 26, No 1. Éva Mathey, Ed. Institute of English and American Studies, University of Debrecen, Hungary, 2020 242 pages ISSN: 1218-7364 Ad American. Journal of American Studies, 2020. Vol. 21. Łukasz Wordliczek, editor-in-chief Institute of American Studies and Polish Diaspora, Jagiellonian University, Krakow, Poland 168 pages ISSN: 1896-9461